Characterization of the fine hand movement in badminton by a smart glove. Issue 4 (3rd July 2020) - Song, Xian; Peng, Yuxin; Hu, Bingcheng; Liu, Wenming
Abstract: In a badminton game, dexterous fine hand movements are essential for the player to perform with extraordinary skill. Thus, this paper proposes a smart glove with proper sensing functions for finger pressures and bending angles for this sport to measure the kinematics and kinetics during the forehand grip and backhand grip. Twenty-one pressure sensors and eleven flex sensors are employed to construct the smart glove, and the measured parameters are then visualized to analyze different grip movements. An athlete and an amateur were selected for the gripping experiments and the measurements was recorded by the smart glove. During forehand gripping, although the total power generated by the amateur (33 N) was higher than for the athlete (29 N), the final shot strength was still unsatisfactory due to the disorderly arranged finger flex angle. In backhand gripping, the incorrectly laid index finger reduced the thumb power of the amateur to 3 N, which weakened the control ability and led to a distorted flying trajectory of the shuttlecock. The differences in kinematics and kinetics between the athlete and the amateur can provide a reference for the badminton learners to perform the correct technical movements. By use of this approach, the proposed system may grant trainers and trainees a better approach to analyze the grip movement.